Numerical investigation of bone remodelling around immediately loaded dental implants using sika deer (Cervus nippon) antlers as implant bed. Issue 4 (12th March 2018) - He, Yun; Hasan, Istabrak; Keilig, Ludger; Fischer, Dominik; Ziegler, Luisa; Abboud, Marcus; Wahl, Gerhard; Bourauel, Christoph
Abstract: This study combines finite element method and animal studies, aiming to investigate tissue remodelling processes around dental implants inserted into sika deer antler and to develop an alternative animal consuming model for studying bone remodelling around implants. Implants were inserted in the antlers and loaded immediately via a self-developed loading device. After 3, 4, 5 and 6 weeks, implants and surrounding tissue were taken out. Specimens were scanned by μCT scanner and finite element models were generated. Immediate loading and osseointegration conditions were simulated at the implant-tissue interface. A vertical force of 10 N was applied on the implant. During the healing time, density and Young's modulus of antler tissue around the implant increased significantly. For each time point, the values of displacement, stresses and strains in the osseointegration model were lower than those of the immediate loading model. As the healing time increased, the displacement of implants was reduced. The 3-week immediate loading model (9878 ± 1965 μstrain) illustrated the highest strains in the antler tissue. Antler tissue showed similar biomechanical properties as human bone in investigating the bone remodelling around implants, therefore the use of sika deer antler model is a promising alternative in implant biomechanical studies.